KARAKTER HABITAT JENIS-JENIS ANGGREK EPIFIT DAN TERESTRIAL DI HUTAN KAMPUNG KANTUMILENA DISTRIK YOKARI KABUPATEN JAYAPURA - MONIKA DEMENA; EDOWARD KRISSON RAUNSAY; VERENA AGUSTINI (JURNAL KEHUTANAN PAPUASIA, 2020)
Orchids can grow in almost all habitats like the ground (terrestrial) and trees/wood (epiphytic). This study aimed at identifying types of epiphytic and terrestrial orchids and their morphological characters. The data collection was performed through observation, survey, documentation, and literature review which were then analyzed through a descriptive quantitative approach. Types of orchids growing in the forest in Kantumilena Village were epiphytic and terrestrial orchids consisting of 10 clans and 20 types. Epiphyte orchids there had 16 types namely Calanthe triplicate (Willemet) Ames, Spathoglottis plicata (Blume), Spathoglottis plicata var alba Blume and Spathoglotis pulchra Schltr. While terrestrial orchids growing in the site consisted of 16 types including Agrostophyllum sp1, Agrostophyllum sp2, Cadetia wariana, Bulbophyllum sp1, Bulbophyllum sp2, Coelogyne Sp1, Coelogyne beccarii (Rchb.f), Dendrobium sp1, Dendrobium sp2, Dendrobium sp3, Dendrobium sp4, Dendrobium spectabile (Blume), Dendrobium lineale Rolfe and Dendrobium controides (T.E.Hunt). The habitats of orchids found in the research site were tree (as host) and ground.